The Principles of the Choice of Management Decisions Based on Fuzzy Logic for Cargo Delivery of Grain to the Seaport - Shramenko, Natalya; Muzylyov, Dmitriy; Karnaukh, Mykola (International Journal of Engineering and Technology, 2018)
In the article, the approach on the development of management decisions for correct selection of trucks is presented, in the conditions of uncertainty and the stochastic nature of demand for transportation of a grain on the section of a supply chain named "a grain elevator - the sea terminal". The main problems arising at delivery of grain cargoes in a supply chain with the participation of automobile and sea transports were described for justification of relevance of the research. A mathematical definition of the researching tasks was made for the search for the rational management decision at forming a rational structure of the park of the trucks transporting the agricultural products to the sea terminal. Numerous management decisions based on the principles of fuzzy logic have been developed. The values of the input factors are proved in the form of a set of linguistic variables for making a correct management decision. Cargo capacity of the ship coming to the port and amounts of grain which is in a reserve directly on the sea terminal are consider to be definite quantitative characteristics of each set of a term-number.Â Â Â